2020
DOI: 10.1002/pc.25927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3 nanofillers in basalt/epoxy composites: Mechanical and tribological properties

Abstract: In this research, effect of Al 2 O 3 nanofillers on mechanical, wear, and hardness characteristics of basalt/epoxy laminate composites were carried out. Composite laminates of basalt/epoxy with different percentage of Al 2 O 3 nano fillers were manufactured by Hand layup method. Mechanical Properties which includes tensile strength, inter laminar shear strength (ILSS), flexural strength, impact strength, and hardness were investigated as per ASTM standards. Wear tests were carried out for different loads with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…The other impact, flexural and interlaminar shear strength properties were enhanced by 10.45%, 20.05% and 18.80% respectively. Vinay et al [176] investigated the effect of Al 2 O 3 nanoparticles on basalt fiber/epoxy polymer composites. The results reveal that the addition of lesser percentage of Al 2 O 3 nanoparticles enhances the ILSS and flexural strength, along with hardness value was increased with increasing percentage of filler concentration.…”
Section: Agnpsmentioning
confidence: 99%
“…The other impact, flexural and interlaminar shear strength properties were enhanced by 10.45%, 20.05% and 18.80% respectively. Vinay et al [176] investigated the effect of Al 2 O 3 nanoparticles on basalt fiber/epoxy polymer composites. The results reveal that the addition of lesser percentage of Al 2 O 3 nanoparticles enhances the ILSS and flexural strength, along with hardness value was increased with increasing percentage of filler concentration.…”
Section: Agnpsmentioning
confidence: 99%
“…Techniques such as vacuumassisted resin transfer molding, compression molding, resin transfer molding, pultrusion, injection molding, and pressure bag molding are used to fabricate thermosetbased composites. [14,15] The thermoplastic-based composites are prepared by using the filament winding, extrusion, thermoforming, injection molding, compression method, foam molding, cold pressing, and co-extrusion techniques. [16][17][18] This review provides information about the properties of some newly identified natural fibers, types of nano-clay and recent progress in the development and characterization of nano-clay added natural fiber composites with specific concern to their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the higher velocity has commanded complex design changes in windows, doors, and rear cabs making the overall weight of the railway vehicle heavier. [6][7][8][9] All these things have undesirably impacted the economy of the railway sector resulting in high manufacturing costs, a large amounts of CO 2 emissions, higher energy consumption and faster track wear. So, in pursuit to become a more efficient transportation system, the railway sector has indeed looking for new technological renovations in terms of lightweight materials systems.…”
Section: Introductionmentioning
confidence: 99%